Use of graphs and taxonomic classifications to analyze content relationships among courseware - Saraiva, Márcio de Carvalho; Medeiros, Claudia Bauzer (Anais do Simpósio Brasileiro de Banco de Dados (SBBD), 2016)
The search for educational content in courseware repositories is laborious and time consuming. There is an abundance of such repositories, and research efforts to facilitate search, but access is guided by keywords and/or terms selected by courseware authors, thus lacking flexibility. The goal of this project is to design and develop a suite of tools to assist users to find, analyze and select pieces of educational content that are relevant to their learning goals. Contributions will be both at the algorithm and software design level, and at the user (application) level.